ISSUE OF GRANT PROPERTY WITHDRAWAL IN ARTICLE 712 OF SHARIA ECONOMIC LAW COMPILATION AND ARTICLE 212 OF ISLAMIC LAW COMPILATION - Junaidi, Junaidi; Surahmi, Mila (Nurani, 2021)
Grant is a unilateral agreement by a grantor that is carried out by the grantor to the grantee who gives goods free of charge to the grantee. This grant is carried out between the grantor and the grantee is still alive and well. In practice, there were many cases where grants were revoked or withdrawn by the grantor for certain reasons. Therefore, this study was conducted to determine the law of withdrawal of grants by the grantors. The research method used is juridical normative and the approach method used in the research is the library research approach. In Article 712 of the Sharia Economic Law Compilation explains that the grant property can be withdrawn by the grant if the grantee approves, whereas, in Article 212 Islamic Law Compilation, the grant cannot be withdrawn under any circumstances, except for a grant related to his child. issue of the difference between the withdrawal of grant property found in the Sharia Economic Law Compilation, if the grantee agrees and voluntarily returns the grant property that has been received and in the Islamic Law Compilation, the grant property can be withdrawn, namely a parent's grant to his child, this is because the grant property can be counted as inheritance as stipulated in Article 211 of Islamic Law Compilation. These two compilation laws are used and applied in the Religious Courts to resolve disputes for Muslim parties.